Interlingual relations as a main factor in mutually enriching languages - Almammadova, Sabina; Rzayeva, Nuriyya (My University, 2024)
There are both reasonable and unjustified ideas in the assumptions and theories about the root commonality in languages of different systems. In this work presented to the readers, special attention is paid to the analysis of the right and wrong aspects of those ideas. Because the contradictions themselves are very important to reveal the truth. Later, in order to eliminate the difficulty in understanding the comparison of roots, it was considered appropriate to provide information about the structure and formation of the genetic roots of the Azerbaijani language itself. This work also analyzes the commonality of monosyllabic roots and words with root-formative composition, as well as parallelisms and motivational similarities. In this analysis, the latest sources of linguistics were used and analyzes and comparisons were made. The mutual development of languages is the reflection of interlingual interaction. The cooperation of nations and peoples affects primarily their language. Conversion of the achievements of scientific and technological achievements into the common property of humanity, the mutual development of their cultural values, in the creation and development of mutually beneficial relations between languages as well as in literature. In the process of its own historical development, the languages have been and continue to be in the process of mutual language interaction.
Keywords: relation; philology; language; cultural values; mutual development